Estimation methods of reference evapotranspiration (ETo) for Uberlândia -MG. - De Lacerda, Zilda C.; Turco, José E.P. [UNESP] (Associação Brasileira de Engenharia Agrícola, 2015)
One approach to verify the adequacy of estimation methods of reference evapotranspiration is the comparison with the Penman-Monteith method, recommended by the United Nations of Food and Agriculture Organization - FAO, as the standard method for estimating ET0. This study aimed to compare methods for estimating ET0, Makkink (MK), Hargreaves (HG) and Solar Radiation (RS), with Penman-Monteith (PM). For this purpose, we used daily data of global solar radiation, air temperature, relative humidity and wind speed for the year 2010, obtained through the automatic meteorological station, with latitude 18° 91' 66 S, longitude 48° 25' 05 W and altitude of 869m, at the National Institute of Meteorology situated in the Campus of Federal University of Uberlandia - MG, Brazil. Analysis of results for the period were carried out in daily basis, using regression analysis and considering the linear model y = ax, where the dependent variable was the method of Penman-Monteith and the independent, the estimation of ET0 by evaluated methods. Methodology was used to check the influence of standard deviation of daily ET0 in comparison of methods. The evaluation indicated that methods of Solar Radiation and Penman-Monteith cannot be compared, yet the method of Hargreaves indicates the most efficient adjustment to estimate ETo.

Uma forma de verificar a adequação de métodos de estimativa da evapotranspiração de referência (ETo) é a comparação com o método de Penman-Monteith, recomendado pela Organização das Nações Unidas para Alimentação e Agricultura – FAO, como método-padrão para estimativa da ETo. Este estudo teve por objetivo comparar os métodos de estimativa da ETo, Makkink (MK), Hargreaves (HG) e Radiação Solar (RS), com o método de Penman-Monteith (PM). Para tanto, utilizaram-se dados diários de radiação solar global, velocidade do vento, temperatura e umidade relativa do ar para o ano de 2010, obtidos na estação meteorológica automática, com latitude de 18º91’66”S, longitude de 48º25’05”W e altitude de 869 m, do Instituto Nacional de Meteorologia, instalado no Câmpus da Universidade Federal de Uberlândia - MG. As análises dos resultados foram feitas para o período diário, utilizando-se da análise de regressão linear y = a x, na qual a variável dependente foi o método de Penman-Monteith, e a independente, as estimativas da ETo pelos métodos avaliados. Utilizou-se da metodologia que verifica a influência do desvio-padrão diário da ETo na comparação dos métodos estudados. Os métodos de Radiação Solar e Penman-Monteith não podem ser comparados, já o método de Hargreaves indica ajuste mais eficiente para a estimativa da ETo.
Métodos de estimativa da evapotranspiração de referência (ETo), para Uberlândia – MG
Keywords: penman-monteith; hargreaves; makkink; solar radiation; penman-monteith; hargreaves; makkink; radiação solar